The Effect of Repeated Reading Method (RRM) in Teaching Reading Comprehension of Narrative Text to the Eighth Grade Students of SMP Negeri 1 Tanah Abang Pali - Tirta Milenia, Voni; Saputri, Kurnia; Larasati, Finza (International Journal of Education Research and Development, 2022)
Abstract. The study aims to investigate the problems: “Whether or not there is any significant effect of using Repeated Reading Method to the eighth-grade students of SMP Negeri 1 Tanah Abang.” Therefore, the objective of the research was to find out whether or not there is any significant effect of using repeated reading method on the students’ reading narrative text to the eighth-grade students’ of SMP Negeri 1 Tanah Abang Pali. The sample of this research was 62 students, divided in to two classes: experimental class and control class. The sample of this research was purposive sampling. The data obtained were analyzed by using independents sample t-test in SPSS (Statistical Package for the Social Science) The result of t-obtained 4.752 was at the significant level p<0.05 for two tailed and degree of freedom (df) was 60, t-table was 2,000. Keywords: Repeated Reading Method , Teaching , Narrative , Reading Comprehension.